(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This article discusses financial management research in major projects published in publications with high influence. Our objective is to discover answers to the following questions from the study: (a) what financial features are being studied? (b) Financial concepts for big project management? The approach utilised was a bibliographical analytic of research articles produced between 2000 and 2013 in the major databases. Our findings show that success is the most prominent element, despite the fact that there is still no agreement on performance evaluation. Whereas in recent years there has been a rise in the quantity of papers in this field, there is also the absence of high-impact journals. Example studies (almost 60%), with only one case covered in most situations, and are the most often utilised approach. Financial efficiency is the most frequently studied topic; however, no consensus has yet been reached on how to assess megaproject performance. A megaproject evaluation is rarely carried out, even though it is the financial objective of any company. Fiscal research and analyses of the key programmes’ financial framework are likewise scarce. Such similar research areas of focus include stakeholder or risk management, as well as public-private partnerships.